If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 8 = 4(x + -4) + -8 Reorder the terms: 8 + -4x = 4(x + -4) + -8 Reorder the terms: 8 + -4x = 4(-4 + x) + -8 8 + -4x = (-4 * 4 + x * 4) + -8 8 + -4x = (-16 + 4x) + -8 Reorder the terms: 8 + -4x = -16 + -8 + 4x Combine like terms: -16 + -8 = -24 8 + -4x = -24 + 4x Solving 8 + -4x = -24 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 8 + -4x + -4x = -24 + 4x + -4x Combine like terms: -4x + -4x = -8x 8 + -8x = -24 + 4x + -4x Combine like terms: 4x + -4x = 0 8 + -8x = -24 + 0 8 + -8x = -24 Add '-8' to each side of the equation. 8 + -8 + -8x = -24 + -8 Combine like terms: 8 + -8 = 0 0 + -8x = -24 + -8 -8x = -24 + -8 Combine like terms: -24 + -8 = -32 -8x = -32 Divide each side by '-8'. x = 4 Simplifying x = 4
| 2x-27=x+5 | | 4+6x=4x-18 | | 6x+4=2x+2 | | 5+7x=-2x-13 | | 5x^3+20x-2=0 | | 1x^2+2x-143=0 | | 8+2m=2(m-6) | | 10(5c-1)-12=48c+10 | | .25x^2-kx+.25=0 | | 25x^2+30x+18=0 | | -9(t+3)=0 | | 4y^2+2y-1=0 | | 4x+14-3x=-8-11 | | 4x-(-2)=8+2x | | -4(y-6)=(-9+y)(2) | | -2x-2x=12-4 | | x^2-kx+16=0 | | 4x^2-28x=49 | | 4x^2-kx+9=0 | | -4+x=2(x-5) | | 3/5=15/6 | | 7x+1+2x-1=90 | | 4h/7-15=177/14+15 | | 13x-131=4x-5 | | 4x+2y=27 | | 7x+1=2x-1 | | 284-4x=41x+24 | | y=x+124x+2y=27 | | a-4=6 | | 0.75=35 | | 81v^2-16= | | 5+-1=7+-5 |